Presence of women in Royal Economic Society of Friends of the Country (1775-1808) (Foro de Educacion, 2024)
In this work we present the performance of women in the work of the Royal Economic Society of Friends of the Country, institutions of the eighteenth century who sought to lift the economy of Spain in that century. Women’s participation in the Royal Economic So- ciety was carried out by the Boards of Damas and supervisory work of the Schools «patriotism» and the first letters. The first schools to be named, according to Campomanes conceived of yarn and fabric and should be established in major cities throughout the kingdom. Participation in the Royal Economic Society from all social classes and genders with equal rights, was a fact. There is no comprehensive study on all of the Royal Economic Society of Friends of the Country, therefore there is no one on women in one way or another took part in them. With this work we present the work done by some.